2006
DOI: 10.1002/chin.200702195
|View full text |Cite
|
Sign up to set email alerts
|

New N4‐Hydroxycytidine Derivatives: Synthesis and Antiviral Activity.

Abstract: New N 4 -Hydroxycytidine Derivatives: Synthesis and Antiviral Activity. -Various derivatives of the antiviral N 4 -hydroxycytidine (Ia) are prepared [cf. (Ib,c) and (II)]. Investigations concerning their pharmacological activity reveal that the acyloxy derivatives of type (I) exhihit potent antiviral effects, whereas the 5'-phosphonates are more cytotoxic than the parent compound (Ia). -(IVANOV, M. A.; ANTONOVA, E. V.; MAKSIMOV, A. V.; PIGUSOVA, L. K.; BELANOV, E. F.; ALEKSANDROVA*, L. A.; Collect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In 2013 we began screening ribonucleoside analogs for activity against alphaviruses and quickly identified N4-hydroxycytidine (identified internally as EIDD-1931) as a lead with activity against the New World encephalitic alphaviruses as well as chikungunya virus. Before this there had been a number of studies demonstrating the activity and favorable cytotoxicity profile of EIDD-1931 in cell culture models of infection [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Pharmacokinetic and distribution studies in mice, rats, ferrets and dogs revealed that EIDD-1931 was orally bioavailable, widely distributed to organs including the lungs and appeared to be actively transported into the CNS where it was quickly anabolized to the active 5′triphosphate [ 7 • , 8 , 10 •• ].…”
Section: Identification Of a Broadly Active Antiviral Agent For The Treatment Of Rna Viral Infectionsmentioning
confidence: 99%
“…In 2013 we began screening ribonucleoside analogs for activity against alphaviruses and quickly identified N4-hydroxycytidine (identified internally as EIDD-1931) as a lead with activity against the New World encephalitic alphaviruses as well as chikungunya virus. Before this there had been a number of studies demonstrating the activity and favorable cytotoxicity profile of EIDD-1931 in cell culture models of infection [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Pharmacokinetic and distribution studies in mice, rats, ferrets and dogs revealed that EIDD-1931 was orally bioavailable, widely distributed to organs including the lungs and appeared to be actively transported into the CNS where it was quickly anabolized to the active 5′triphosphate [ 7 • , 8 , 10 •• ].…”
Section: Identification Of a Broadly Active Antiviral Agent For The Treatment Of Rna Viral Infectionsmentioning
confidence: 99%
“…The synthesis of several of the pyrimidine nucleotides was reported in previous studies of the P2Y receptor (3, 5, 6, 8, 10, 19, 21, and 26). [14][15][16] 5-Iodouridine 34 was available from commercial sources, while the 4-methoxyimino derivative 36 and (S)-methanocarbauridine 41 were prepared as described, 19,25 and compounds 37-39 were prepared by the same procedure as 36. Compounds 34 and 36 were converted to the R,β-methylene diphosphonate analogues 11 and 16, respectively, by a carbodiimide condensation.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 36 was synthesized as reported. 19,25 Other reagents and solvents were purchased from Sigma-Aldrich (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations